The Celluloid Waltz: Memories of the Fairground Carousel - Magdanz, Teresa (Canadian University Music Review / Revue de musique des universités canadiennes, 2003)
This paper explores the idea that the fairground carousel and waltz are tightly linked in the popular imagination. But this ubiquitous cultural convention has come with a price. The decline in fairground attendance from the 1920s and on dovetailed with the increasing reenactment in movies and music of such entertainments and space. And the prime structure motivating such docudramatic images was a kind of public collective memory, often at odds with actual, historical experience.